Problems and Challenges of Avramović Stabilization Program Quarter of a Century Later - Šoškić, Dejan (Panoeconomicus, 2022)
Avramović accepted a position of a governor of Central bank of Yugoslavia (at that time, consisted of Republic of Serbia and Republic of Montenegro) in 1994. He has successfully executed one of the most effective anti-inflation programs in an adverse financial environment and without international support. This paper deals with some of the basic problems Avramović has faced twenty five years ago, most of which have left visible consequences up to present day. They still nowadays present important weaknesses of Serbian monetary and financial system. First of those problems is low institutional independence of Serbian central bank. Second problem Avramović was facing was lack of confidence in the banking system. Third problem Avramović was facing at the time of his Program was lack of confidence in the local currency. These features, although less pronounced, still remain a burden for Serbian financial system. They increase lending risks, weaken monetary policy tools, and decrease rates of growth to this day. Keywords: Anti-inflation program, Dragoslav Avramović, Dollarization, Monetary policy, Central bank independence. JEL: E58, G28, G21, N14.